Psychological Immunity and Its Relationship to Social Support among Students of the College of Physical Education and Sports Sciences, University of Diyala - Sara Akram Hameed; Noor Essam Mohammed; Firas Abdel Moneim (Zanco Journal of Human Sciences, 2025)
The current study aims at the concept of psychological immunity in psychology, which is one of the positive concepts that maintain the student's balance between him and his environment and social support. "It is one of the preventive processes that mean the ability of the athlete to overcome stressful situations and that immunity protects him from the emergence of other conditions such as blood pressure, sugar, depression, collapse and others in addition to the continuous destruction of the capabilities of society and its property, and the research problem was characterized by weak psychological immunity generates a great danger to the health of the student and his balance as threatening his being because of the resulting negatives such as weak ability to adapt and low level of performance and motivation to study and a sense of academic exhaustion and one of the objectives of the current research is to identify psychological immunity And social support among students of the College of Physical Education and Sports Sciences - University of Diyala The research community and its sample, which numbered (235) male and female students, as the research sample was represented by (5) people only students, and they were randomly selected by lottery, and thus the sample adopted in the research for students is (174) students, as their percentage of the sample was (74.04%) of the original community, while the sample of the exploratory experiment was (24) students selected by lot from all student divisions, as their percentage was (13.79%), After reviewing a number of available scales, the researchers relied on the psychological immunity scale of (Osama Abboud Khudair, 2016) and the social support scale of (Nadia Muhammad Razouki, 2013).